Bananas, beaches and bases: making feminist sense of international politics - Enloe, Cynthia H. (University of California Press, 2014)
In this brand new radical analysis of globalization, Cynthia Enloe examines recent events—Bangladeshi garment factory deaths, domestic workers in the Persian Gulf, Chinese global tourists, and the UN gender politics of guns—to reveal the crucial role of women in international politics today. With all new and updated chapters, Enloe describes how many women's seemingly personal strategies—in their marriages, in their housework, in their coping with ideals of beauty—are, in reality, the stuff of global politics. Enloe offers a feminist gender analysis of the global politics of both masculinities and femininities, dismantles an apparently overwhelming world system, and reveals that system to be much more fragile and open to change than we think.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; inégalités; pol5480; politique internationale; premier cycle; ressource en ligne; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; travail

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif